Human well- being and the natural environment - "Dasgupta, Partha" (New Delhi, 2001)
In This Book The Author Explores Ways To Measure The Quality Of Life. Today, Quality-Of-Life Indices Brokes Political Arguments And Together Form A Coin That Even Political Arguments And Together Form A Coin That Even Helps Purchase Economic And Social Policy.
Keywords: Natural resources